A Review of Central Bank Digital Currency Application in Indonesia - Faiz, Ihda Arifin; Taib, Fauziah Md; Harwood, Jamal; Triono, Dwi Condro (Islamic Research, 2024)
The study explores the prospects and possibilities of the application of a Central Bank Digital Currency (CBDC) in Indonesia, which is widely discussed by Bank Indonesia (BI), using a critical approach from an Islamic perspective. As digital payments and technology disruptions radically change people’s behaviour and the way they conduct transactions, the issue is critical to the existing literature and promoting policy. Using a descriptive-qualitative method, the study identifies the existing literature and the implementation challenges in the Indonesian context, further enhanced by incorporating Islamic viewpoints as a core value. The study revealed that cash-like money still dominates the existing currency distribution, and the socio-economy, including the infrastructure in daily transactions, still relies on the traditional monetary system. The implementation of CBDC in the short term remains risky. From an Islamic perspective on the monetary system, Indonesia does not adopt gold and silver standards as underlying assets for currency issuances. It deviates from the Sharia rules and is a core issue for the monetary system.